Clinical course of pancreas cancer diagnosed after spleen-preserving distal pancreatectomy with borderline lesion: two case reports - Byeong Gwan Noh; Hyung Il Seo; Young Mok Park (Korean Journal of Clinical Oncology, 2024)
Distal pancreatectomy with splenectomy is considered the standard operation for pancreas tail and body cancer. However, splenectomy may be option for benign or low-grade malignant tumors including mucinous cystadenoma and intraductal papillary mucinous neoplasm. If spleen-preserving distal pancreatectomy (SPDP) with borderline lesion is performed and pancreas cancer is diagnosed on postoperative pathologic finding, if it is R0 resection, the necessity of additional splenectomy remains questionable. The authors would like report two clinical cases diagnosed as pancreatic cancer on postoperative pathology after SPDP and under observation without additional splenectomy.